Improved face mask testing system - Richard A Brandt (Measurement + Control, 2023)
A new way to measure the penetration efficiency of a face mask is introduced. It has a number of advantages over the currently used measurement systems in which a stationary mask is impacted with a moving aerosol during which the upstream and downstream particle concentrations are compared. The equivalent system described here instead moves a mask through a stationary aerosol in a closed chamber and compares the particle concentrations before and after the movement of the mask. This system provides many advantages, such as greater simplicity, greater accuracy, an exact constant aerosol flow speed through a mask, more easily made concentration measurements, more realistic impacts, more controlled averaging, the absence of the need for preliminary impacts during flow stabilization, and a lower cost. A laboratory prototype of the system has been fabricated and seen to perform as expected. Data obtained from this prototype are displayed, analyzed, and used to demonstrate the consistency and repeatability of the system. A portable fully-automated compact prototype has also been designed and fabricated. This device can be easily operated, and the total time required to test a mask, from material insertion to result display, is only a few minutes.